Sensitivity of the Neuroendocrine Stress Axis in Metabolic Diseases - Cozma, Diana; Siatra, Panagiota; Bornstein, Stefan R.; Steenblock, Charlotte (Hormone and Metabolic Research, 2024)
Metabolic diseases are prevalent in modern society and have reached pandemic proportions. Metabolic diseases have systemic effects on the body and can lead to changes in the neuroendocrine stress axis, the critical regulator of the body’s stress response. These changes may be attributed to rising insulin levels and the release of adipokines and inflammatory cytokines by adipose tissue, which affect hormone production by the neuroendocrine stress axis. Chronic stress due to inflammation may exacerbate these effects. The increased sensitivity of the neuroendocrine stress axis may be responsible for the development of metabolic syndrome, providing a possible explanation for the high prevalence of severe comorbidities such as heart disease and stroke associated with metabolic disease. In this review, we address current knowledge of the neuroendocrine stress axis in response to metabolic disease and discuss its role in developing metabolic syndrome.
Keywords: HPA axis; adipose tissue; obesity; metabolic diseases; obesity